Double‐focusing mixing jet for XFEL study of chemical kinetics. (6th October 2014) - Wang, Dingjie; Weierstall, Uwe; Pollack, Lois; Spence, John
<x xml:space="preserve">Abstract</x> Several liquid sample injection methods have been developed to satisfy the requirements for serial femtosecond X‐ray nanocrystallography, which enables radiation‐damage‐free determination of molecular structure at room temperature. Time‐resolved nanocrystallography would combine structure analysis with chemical kinetics by determining the structures of the transient states and chemical kinetic mechanisms simultaneously. A windowless liquid mixing jet device has been designed for this purpose. It achieves fast uniform mixing of substrates and enzymes in the jet within 250 µs, with an adjustable delay between mixing and probing by the X‐ray free‐electron laser beam of up to 1 s for each frame of a `movie'. The principle of the liquid mixing jet device is illustrated using numerical simulation, and experimental results are presented using a fluorescent dye.